(untitled) (Innovaciones Educativas, 2022)
The objective of the following research was to evaluate the way in which socio-scientific skills are treated in the classes of the agribusiness specialty in laboratory work. The study was carried out under a dominant qualitative approach. The study subjects were six teachers from the aforementioned area of ​​a technical college in Costa Rica and the entire student population (32 students). To collect the information, a performance record was used for content analysis, observations and questionnaires addressed to both teachers and students of the specialty. The results were analyzed and triangulated to finally represent them graphically in order to facilitate their interpretation. The results indicated that the socio-scientific skills proposed by the Ministry of Public Education (MEP) are explicitly cognitive, attitudinal and procedural, and also implicitly social skills are proposed. Regarding the application, it was identified that social and attitudinal skills (knowing how to act and knowing how to be) presented a good development in laboratory work. In contrast, cognitive and procedural skills (manual and investigative) presented less development, despite the fact that this area of ​​specialty is eminently applied.